2022
DOI: 10.1021/acsami.2c05168
|View full text |Cite
|
Sign up to set email alerts
|

Antiferroelectric Phase Diagram Enhancing Energy-Storage Performance by Phase-Field Simulations

Abstract: Antiferroelectric materials have shown potential applications in energy storage. However, controlling and improving the energy-storage performance in antiferroelectric remain challenging. Here, a domain structure and energy-storage performance diagram for Pb­(Zr1–x Ti x )­O3 (x ≤ 0.1) single crystal are investigated via phase-field simulations. Controlling the ratio of domain wall coefficients λ and g can tune the periodicities of the antiferroelectric stripe domain and generate a complicated topological doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…It has been proved that elemental modification is an efficient strategy for the enhancement of electrical and polarization properties. The recoverable energy storage density ( W reco ), loss density ( W loss ), and total energy density ( W total ), as well as the energy conversion efficiency (η) can be calculated according to eqs - W normalr normale normalc normalo = P normalr P max E .25em normald P W normalt normalo normalt normala normall = 0 P max E .25em normald P η = W r e c o W normalr normale normalc normalo + W normall normalo normals normals × 100 % = W r e c o W t o t a l × 100 % where P max is the maximum polarization intensity of films, and P r is the remnant polarization intensity. In recent years, research related to the energy storage behavior has been focused on the phase transition properties regarding the energy storage scenes. , It has been reported that high energy density could be obtained due to their large spontaneous polarization and electrode modulation. , <...…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that elemental modification is an efficient strategy for the enhancement of electrical and polarization properties. The recoverable energy storage density ( W reco ), loss density ( W loss ), and total energy density ( W total ), as well as the energy conversion efficiency (η) can be calculated according to eqs - W normalr normale normalc normalo = P normalr P max E .25em normald P W normalt normalo normalt normala normall = 0 P max E .25em normald P η = W r e c o W normalr normale normalc normalo + W normall normalo normals normals × 100 % = W r e c o W t o t a l × 100 % where P max is the maximum polarization intensity of films, and P r is the remnant polarization intensity. In recent years, research related to the energy storage behavior has been focused on the phase transition properties regarding the energy storage scenes. , It has been reported that high energy density could be obtained due to their large spontaneous polarization and electrode modulation. , <...…”
Section: Introductionmentioning
confidence: 99%
“…High-performance ferroelectric oxides are critical components in the current electronics industry because they have outstanding electrical properties, including ferroelectricity, piezoelectricity, pyroelectricity and dielectricity. They are widely applied in high-efficiency memories [32][33][34][35] , microsensors [36,37] , high-frequency filters [38,39] , energy harvesting systems [40,41] , high-energy-density capacitors [42][43][44][45] , ultrasonic medical treatment [46,47] and other related devices [48][49][50][51] , and are also expected to be applied in the field of high-temperature superconductivity [52,53] . However, perovskite ferroelectrics are generally considered to be brittle and unbendable [54,55] .…”
Section: Introductionmentioning
confidence: 99%
“…[38] To further establish the validity of this model, phase-field simulations were performed with more details of the method provided in Supplemental Materials. [39][40][41][42] A two-phase model was employed initially for the BF-BT matrix due to the lack of potential functions. [18] Although the phase ratio is slightly different from the experimental observation, the simulations nonetheless provide theoretical guidance to understand the experimental results.…”
mentioning
confidence: 99%